Deskripsi Minat Membaca Peserta Didik Kelas IV di SDN 15 Sungai Pinyuh - Sofi Yunita (PT. ALHAFI BERKAH INDONESIA, 2024)
Low reading interest in students will affect the low knowledge and insight of students. High reading interest will cause students to feel more enthusiastic and happy when learning. The more reading, the more information will be absorbed so that it will increase knowledge and insight. With full awareness, students will be more active in reading and active in participating in learning. This research is a qualitative research method with a descriptive research type. Data collection techniques are carried out by means of background, sources, background methods collected through natural settings. This study uses data collection techniques, namely interviews. Based on the results of the study, the reading interest of fourth grade students at SDN 15 Sungai Pinyuh is classified as moderate because this researcher shows that the reading interest of fourth grade students at SDN 15 Sungai Pinyuh still needs to be improved. Students are less motivated to read due to the lack of interesting reading books and less varied reading activities. Factors that influence reading interest are the availability of books at home, parental support, and literacy activities at school.